2x + 3 = -7
3(x + 5) -2 = 2(x - 1) -5
5(x - 7) -3 (x - 3) +17 = 11
-3(x + 1) -2 (1 - 2x) - (x +5) = 17- x
Răspunsuri la întrebare
Răspuns de
0
1) 2x=-7-3
2x=-10
X=-5
2)3x+15-2=2x-2-5
3x-2x=-2-5-15+2
X=-20
3)5x-35-3x+9+17=11
2x-9=11
2x=20
X=10
4)-3x-3-2+4x-x-5=17-x
-10=17-x
X=27
Răspuns de
1
2x+3=-7
2x=-7-3
x=-10/2
x=-5
3(x+5)-2=2(x-1)-5
3x+15-2=2x-2-5
3x-2x=-7-13
x=-20
5(x-7)-3(x-3)+17=11
5x-35-3x+9=11-17
2x=-6+26
x=20/2
x=10
-3(x+1)-2(1-2x)-(x+5)=17-x
-3x-3-2+4x-x-5+x=17
x=17+10
x=27
2x=-7-3
x=-10/2
x=-5
3(x+5)-2=2(x-1)-5
3x+15-2=2x-2-5
3x-2x=-7-13
x=-20
5(x-7)-3(x-3)+17=11
5x-35-3x+9=11-17
2x=-6+26
x=20/2
x=10
-3(x+1)-2(1-2x)-(x+5)=17-x
-3x-3-2+4x-x-5+x=17
x=17+10
x=27
MihaiStocheci1:
Ai copiat gresit la a 3 a. Este +17 nu -17 :)
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă